Enhanced temporal but not attentional processing in expert tennis players - Overney, L. S.; Blanke, O.; Herzog, M. H. (PLOS ONE, 2008)
In tennis, as in many disciplines of sport, fine spatio-temporal resolution is required to reach optimal performance. While many studies on tennis have focused on anticipatory skills or decision making, fewer have investigated the underlying visual perception abilities. In this study, we used a battery of seven visual tests that allowed us to assess which kind of visual information processing is performed better by tennis players than other athletes (triathletes) and non-athletes. We found that certain time-related skills, such as speed discrimination, are superior in tennis players compared to non-athletes and triathletes. Such tasks might be used to improve tennis performance in the future.